2021
DOI: 10.1097/lgt.0000000000000576
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid Amplification Testing Compared With Cultures, Gram Stain, and Microscopy in the Diagnosis of Vaginitis

Abstract: Objective The aim of the study was to evaluate the performance of nucleic acid amplification testing (NAAT) for the diagnosis of vulvovaginal candidiasis (VVC), bacterial vaginosis, and Trichomonas vaginalis. Methods A cross-sectional analysis of women with (n = 200) and without (n = 100) vulvovaginal symptoms was enrolled from outpatient gynecology offices and a vulvovaginal referral clinic. Vaginal swabs were analyzed by wet mount microscopy, yeast cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…It has been reported that WMM with low sensitivity (48.50%) are prone to underdiagnosis of VVC. 26 WMM, a diagnostic method that cannot distinguish strain species is difficult to meet the needs of clinical precision medicine. Interestingly, the diagnostic performance of PCR-QDFA for all Candida strains within the PCR-QDFA targets was comprehensively evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that WMM with low sensitivity (48.50%) are prone to underdiagnosis of VVC. 26 WMM, a diagnostic method that cannot distinguish strain species is difficult to meet the needs of clinical precision medicine. Interestingly, the diagnostic performance of PCR-QDFA for all Candida strains within the PCR-QDFA targets was comprehensively evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…17 Nucleic acid amplification testing outperforms microscopy for both yeast vaginitis and trichomoniasis, but microscopy was found to be more sensitive than culture or nucleic acid amplification testing for bacterial vaginosis diagnosis in one study. 23 This may suggest a role for bacterial vaginosis nucleic acid amplification testing if microscopy is negative for symptomatic patients. Although several molecular diagnostic tests have FDA clearance and published clinical validity compared with standard testing modalities, they are not widely incorporated into clinical guidelines; thus, many payer policies may continue to deny coverage for nucleic acid amplification testing among nonpregnant patients.…”
Section: The Modern Approachmentioning
confidence: 99%
“…17 Nucleic acid amplification testing outperforms microscopy for both yeast vaginitis and trichomoniasis, but microscopy was found to be more sensitive than culture or nucleic acid amplification testing for bacterial vaginosis diagnosis in one study. 23 This may suggest a role for bacterial vaginosis nucleic acid amplification testing if microscopy is negative for symptomatic patients.…”
Section: The Modern Approachmentioning
confidence: 99%
“…• втрату або зменшення кількості Lactobacillus із одночасним збільшенням чисельності інших видів бактерій -переважно G. vaginalis, анаеробних грамнегативних паличок [22,32,33], • утворення летких амінів новою бактеріальною мікробіотою і зниження продукування молочної кислоти [31], • підвищення рН піхви понад 4,5 (нормальний рН піхви жінок репродуктивного віку зазвичай коливається від 4,0 до 4,5). Відсутність клінічних ознак запалення є підставою для терміну «вагіноз», а не «вагініт».…”
Section: патологічні зміни у вагінальному середовищіunclassified